Effects of electrical stimulation of the habenula on the modulation of emotional responses in Wistar rats - María Laura Herrera (Acta Colombiana de Psicología, 2018)
Deep brain stimulation is a widely-used approach to the treatment of neurologic and neuropsychiatric diseases. However, its mechanisms remain unclear. There are few systematic studies relating variations on electrical stimulation parameters (frequency, intensity, pulse duration) and behavioral outcome. The habenula relates to emotional behavior and is a main target for chronic pain and depression stimulation treatment. The relation between habenular electrical stimulation and performance in behavioral tests has not been clearly defined. In order to assess the emotional effects of chronic habenular electrical stimulation, Wistar male rats were unilaterally implanted with electrodes aimed to the lateral habenula and assigned to low (10-80 μA) or high (120-260 μA) intensity and low (80-150 Hz) or high (240-380 Hz) frequency conditions: BIBF-AIBF-BIAF-AIAF. They received electrical stimulation 15 minutes/day for three consecutive days and on the fourth day were tested in the elevated plus maze and the open field. The results of these study show that BIAF stimulation has a possible anxiolytic-like effect when compared to BIBF and AIBF (increase in the percentage of open-arms time, entries into the open-arms and total-distance-run in the open-arms). This is not due to any changes in locomotion (total-distance-run and open field exploration). It is concluded that frequency is more important than intensity for behavioral modification. This could explain some previous inconsistent results. The data also suggest that these parameters of stimulation have no anxiogenic effects. The role for dopaminergic and serotonergic systems must be subsequently evaluated as well as potential anxiogenic-like effects of low frequency stimulation.